Experimental Investigation of The Influence of Mechanical Forced Vibrations and Heat Flux on Coefficient of Heat Transfer - Bash, Adil; Alkumait, Aadel; Yaseen, Hamza (Science Journal of University of Zakho, 2018)
The aim of this paper to verify the influence of vertical forced vibration on the coefficient of heat transfer of the laminar internal flow in a spiral fluted tube. With adopted the water as a working fluid, and flowing Reynolds numbers at the entrance between 228 and 1923, the tube heated under constant heat flux levels ranging from 618-3775 W/m2. The frequencies of vibration ranging from 13 to 30 Hz, and the amplitudes of vibration from 0.001 to 0.002 mm. The results appeared that the coefficient of heat transfer significantly affected by mechanical forced vibration in a flowing of the heated tube. When the vibration amplitude increases, the Nusselt number Significantly increases, with the maximum increases of 8.4% at the amplitude of vibration 0.0022 mm and the frequency 13 Hz. Generally, the coefficient of heat transfer increases with increasing Reynolds number and heat flux. At last, by using the parameters of vibration amplitude, frequency, heat flux and Reynolds number, a new correlation has been derived depends on experimental data.
Keywords: Frequency of Vibration; Amplitude; Non-Dimensional Coefficient of Heat Transfer; Reynolds Number